Solid‐state nuclear magnetic resonance study of polymorphism in tris(8‐hydroxyquinolinate)aluminium. (27th March 2021) - Cross, Callum; Cervini, Luca; Halcovitch, Nathan R.; Griffin, John M.
Abstract: Tris(8‐hydroxyquinolinate)aluminium (Alq3 ) is a metal–organic coordination complex, which is a widely used electroluminescent material in organic light‐emitting diode technology. Crystalline Alq3 is known to occur in five polymorphic forms (denoted α, β, γ, δ, and ε), although the structures of some of these polymorphs have been the subject of considerable debate. In particular, the structure of α‐Alq3, which is a model for the local structure in amorphous films used in devices, is highly complex and has never been conclusively solved. In this work, we use solid‐state nuclear magnetic resonance (NMR) and density functional theory (DFT) calculations to investigate the local structure of four Alq3 samples. We find that the first structure proposed for α‐Alq3 is inconsistent with all of the samples studied, and DFT calculations further suggest that this structure is energetically unfavourable. Instead, samples containing the meridional ( mer ) isomeric form are found to contain local structures consistent with ε‐Alq3, and a sample containing the facial ( fac ) isomeric form is consistent with a mixture of γ‐Alq3 and δ‐Alq3 . We also investigate the influence of different strategies for dispersion correction in DFT geometry optimisations. We find that a recently proposed modified semiempirical dispersion correction scheme gives good agreement with experiment. Furthermore, the DFT calculations also show that distinction between mer and fac isomers on the basis of ηQ that has been assumed in previous work is not always justified. Abstract : Tris(8‐hydroxyquinolinate)aluminium (Alq3) is a metal–organic coordination complex, which is a widely used electroluminescent material in organic light‐emitting diode technology. Crystalline Alq3 is known to occur in five polymorphic forms (denoted α, β, γ, δ, and ε), although the structures of some of these polymorphs have been the subject of considerable debate. In particular, the structure of α‐Alq3, which is a model for the local structure in amorphous films used in devices, is highly complex and has never been conclusively solved.